2017
DOI: 10.1155/2017/4353510
|View full text |Cite
|
Sign up to set email alerts
|

How AMPK and PKA Interplay to Regulate Mitochondrial Function and Survival in Models of Ischemia and Diabetes

Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is a conserved, redox-activated master regulator of cell metabolism. In the presence of oxidative stress, AMPK promotes cytoprotection by enhancing the conservation of energy by suppressing protein translation and by stimulating autophagy. AMPK interplays with protein kinase A (PKA) to regulate oxidative stress, mitochondrial function, and cell survival. AMPK and dual-specificity A-kinase anchoring protein 1 (D-AKAP1), a mitochondrial-directed scaffold of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 121 publications
1
47
0
Order By: Relevance
“…It has been reported that there was evidence of AMPK activation by increasing AMPK phosphorylation at Thr172 in the retina and optic nerve in glaucomatous DBA/2J mice 14,51 . Also, it has been proposed that AMPK uncouples PKA from D-AKAP1 (AKAP140/149 and other splice variants AKAP121, sAKAP84) to promote mitochondrial fission and mitophagy 52 . Furthermore, AMPK is associated with the regulation of Drp1 phosphorylation 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there was evidence of AMPK activation by increasing AMPK phosphorylation at Thr172 in the retina and optic nerve in glaucomatous DBA/2J mice 14,51 . Also, it has been proposed that AMPK uncouples PKA from D-AKAP1 (AKAP140/149 and other splice variants AKAP121, sAKAP84) to promote mitochondrial fission and mitophagy 52 . Furthermore, AMPK is associated with the regulation of Drp1 phosphorylation 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…AMPK can also phosphorylate p53 at S15 [114], thereby potentiating its activity in enhancing mitochondrial metabolism. Furthermore, it is noteworthy that although cell type-dependently, AMPK [115], p53 [116] AKT [117], and mTOR [118] activation can trigger mitochondrial fusion which may also be a possible explanation for enhanced mitochondrial activity. Since PARP inhibition alone do not induce CPD formation, we must take into account that the PARPi-mediated changes in the non-irradiated cells are mediated by CPD-independent mechanisms either through autophagy induction and/or NAD + prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial fusion/mitophagy is related to AMPK, a key energy sensor that regulates cellular metabolism to maintain energy homeostasis [26,27]. Cui et al showed that melatonin treatment reduced the apoptosis of human umbilical vein endothelial cells by promoting mitochondrial fusion through activation of the AMPK pathway [13].…”
mentioning
confidence: 99%